2016
DOI: 10.1016/j.stem.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic Metabolism Plays a Functional Role in Regulating Human Pluripotent Stem Cell State

Abstract: SUMMARY The rate of glycolytic metabolism changes during differentiation of human embryonic stem cells (hESCs) and reprogramming of somatic cells to pluripotency. However, the functional contribution of glycolytic metabolism to the pluripotent state is unclear. Here we show that naive hESCs exhibit increased glycolytic flux, MYC transcriptional activity, and nuclear N-MYC localization relative to primed hESCs. This status is consistent with the inner cell mass of human blastocysts, where MYC transcriptional ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
269
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 240 publications
(283 citation statements)
references
References 48 publications
10
269
0
Order By: Relevance
“…At the same time, human and mouse naïve PSCs exhibit increased OXPHOS (Takashima et al, 2014;Zhou et al, 2012). Now Gu et al (2016) demonstrate that human naïve PSCs, both newly derived and those cultured in previously reported reversion conditions (Takashima et al, 2014;Theunissen et al, 2014), in addition to higher mitochondrial oxygen consumption also display elevated glycolytic rates. Human naïve PSCs consumed more glucose, produced more lactate, and incorporated more glucose carbons into lactate and into purine and pyrimidine nucleotides, implying increased flux towards glycolysis and the PPP.…”
Section: Main Textmentioning
confidence: 65%
See 4 more Smart Citations
“…At the same time, human and mouse naïve PSCs exhibit increased OXPHOS (Takashima et al, 2014;Zhou et al, 2012). Now Gu et al (2016) demonstrate that human naïve PSCs, both newly derived and those cultured in previously reported reversion conditions (Takashima et al, 2014;Theunissen et al, 2014), in addition to higher mitochondrial oxygen consumption also display elevated glycolytic rates. Human naïve PSCs consumed more glucose, produced more lactate, and incorporated more glucose carbons into lactate and into purine and pyrimidine nucleotides, implying increased flux towards glycolysis and the PPP.…”
Section: Main Textmentioning
confidence: 65%
“…This is in contrast with the reduction of glycolytic metabolism previously found in mouse naïve PSCs (Zhou et al, 2012). Gu et al (2016) suggest that this discrepancy may be due to species-related differences. In particular, they observed that nuclear C-MYC, which promotes glucose metabolism, is higher in primed PSCs in mice, while it is higher in naïve PSCs in humans.…”
Section: Main Textmentioning
confidence: 95%
See 3 more Smart Citations